DESIGNING THE IDENTITY OF THE VISUAL ART CENTER PURWOREJO AS A VISUAL COMMUNICATION MEDIUM - Aida Arifiani, Aida Arifiani; Andreas Slamet Widodo, Andreas Slamet Widodo (Universitas Negeri Semarang, 2025)
Purworejo is a regency in Central Java that has one of the tourism and creative economy sectors that carries the concept of heritage and sustainability, namely the Art Center. The Art Center is a means of education, conservation, and showroom for all artists in Purworejo Regency. However, its visual identity has not been optimal until now. Therefore, design is needed to create a strong and consistent visual identity to support the image of the creative area at the regency level and in line with SDGs point 11, namely sustainable cities and communities. This research uses the design thinking design method with the stages of the process of emphatize, define, ideate, prototype and test with Charles S Pierce's semiotic analysis. The main idea of ​​the design comes from the local potential of Purworejo, namely the Kaprajan Batik motif which is applied to the main media in the form of a Graphic Standard Manual. Through this design, it is expected to be able to create an attractive visual identity and foster visitors' interest in coming to the Art Center.